2019
DOI: 10.1177/1369433219895358
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of deficient reinforced concrete columns subjected to concentric and eccentric loads

Abstract: In this research, different techniques of repair of deficient reinforced concrete columns are compared. These include carbon fiber–reinforced polymer sheets, steel jackets, and reinforced concrete jackets. The experimental investigation includes testing of 16 deficient columns of dimensions 150 × 150 × 800 mm subjected to concentric and eccentric loading up to failure. Two main variables are considered: the load eccentricity and the strengthening technique. The experimental results showed that the three streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This behavior can be because of the constraint imposed by the loading plates at the two ends of the specimens causing the cracks to start at the top and bottom of the columns. The same behavior of cracking was reported in previous research [9,38,39]. As the loading increased, the width of the cracks increased, and new cracks started to develop propagating towards the mid height of the specimen.…”
Section: Modes Of Failure and Crack Patternssupporting
confidence: 85%
“…This behavior can be because of the constraint imposed by the loading plates at the two ends of the specimens causing the cracks to start at the top and bottom of the columns. The same behavior of cracking was reported in previous research [9,38,39]. As the loading increased, the width of the cracks increased, and new cracks started to develop propagating towards the mid height of the specimen.…”
Section: Modes Of Failure and Crack Patternssupporting
confidence: 85%
“…The results showed that all of the strengthening techniques improved the ultimate loads. Also, CFRP wrapping experienced high ductility for both cases of loading [9]. Naji et al (2021) reviewed the rehabilitation and strengthening techniques for reinforced concrete columns.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement is ascribed to the high strength-to-weight ratio, high corrosion resistance, easier application in narrowed spaces, lessening labor costs, and easiness in site handling for FRP composites (Ali et al, 2020; Aslam et al, 2021; El Ouni and Raza, 2021; Ilki et al, 2008; Pour et al, 2019; Raza et al 2019, 2021a, 2021b, 2021c; Raza and Rafique, 2020; Rafique et al, 2021). The FRP composites are advanced materials for the strengthening and stiffening of the structural elements (Ali and Forth, 2021; El-Kashif et al, 2020; Huang et al, 2020; İşleyen et al, 2021; Tu et al, 2019; Wang et al, 2015; Wu et al, 2006; Zhang et al, 2020; Li and Jiao, 2021; Zhu et al, 2005; Zeng et al, 2021). In this context, several studies were performed to investigate the axial compression performance of CFRP-wrapped concrete in a circular section (Al-Nimry and Neqresh, 2019; Cui and Sheikh, 2010; Ferrotto et al, 2018; Jiang and Teng, 2007; Khan et al, 2020; Lam and Teng, 2003, 2004; Lam et al, 2006; Lin and Teng, 2019; Mirmiran et al, 1998; Spoelstra and Monti, 1999; Shahawy et al, 2000; Smith et al, 2010; Teng et al, 2009; Rousakis et al, 2012; Xiao and Wu, 2003; Youssf et al, 2017).…”
Section: Introductionmentioning
confidence: 99%